English phonetics and phonology : A practical course - Roach, Peter (UK Cambridge University Press, 2009)
It includes updated references, fuller coverage of intonation, and a new chapter on different varieties of English with illustrative recorded material. At the end of each chapter in the book there are notes giving information on further reading, discussion of the more challenging issues, written exercises and, where appropriate, suggestions for teachers.
Includes bibliographical references and index
Keywords: Cơ bản